Use of a Real Time PCR Assay to Assess the Effect of Pulsed Light Inactivation on Bacterial Cell Membranes and Associated Cell Viability. (1st February 2016) - Garvey, Mary; Stocca, Alessia; Rowan, Neil
ABSTRACT: : Research into more rapid and effective means of disinfecting water has become necessary due to the recognition that not all pathogenic species are being removed by chemical means. There is an extent of research highlighting the benefits of pulsed light for the disinfection of water. This study aims to determine the ability of a real time polymerase chain reaction assay to evaluate microbial inactivation of pulsed light treated cells. Findings show that pulsed light is a more rapid means of inactivating test species than standard UV lamp systems. A linear relationship between cell number and polymerase chain reaction amplification was obtained. A difference in threshold value (Ct) of approximately 4 ( p ≤ 0.05) was obtained for DNA amplification following the addition of the dye for pulsed ultrviolet (PUV)‐treated Bacillus cells. Membrane protein leakage proved an effective means of determining membrane damage for both Bacillus and E. coli test species following PUV treatment. This membrane damage was not evident for cells exposed to low pressure ultraviolet (LPUV). Findings describe suggest that PUV treatment induced a viable but nonculturable state in treated cells.